Managerial Incentives, Internalization, and Market Valuation of Multinational Firms - Mishra, Chandra S.; Gobeli, David H. (Journal of International Business Studies, 1998)
This paper examines the role of firm technology investment, in concert with managerial incentives alignment, to explain the relative market value compared to the accounting value for a multinational firm. The results are consistent with internalization theory in that greater multinationality corresponds to a higher valuation of the firm if technology investment is high, and the impact is even greater if managerial incentives alignment is high as well. However, greater multinationality alone does not correlate to a significantly greater value, which differs from the tenets of imperfect capital markets theory.